ANALISIS LIFESTYLE MAHASISWA STIE âADI UNGGUL BHIRAWAâ SURAKARTA TERHADAP KEMANDIRIAN - Irma Susanti, Nani; Wariati, Ambar (KELOLA, 2013)
The Title Of This Research is The Analysis of Lifestyle Of STIE âAUBâ Students of Surakarta on the independency. The research object is STIE âAUBâ students. Data are taken by using accident stratified proporsional random sampling from 300 respondents. This study uses analysis tools such as 1) descriptive statistical analysis 2) Test of validity and realibility of the instrument 3) Regression analysis 4) T test, and 5) Determination test. Descriptive Analysis describes the charactersistics of the respondents by age, living costs, parents work, gender, serial number of children in the family and leisure time activities. Descritive analysis describes the regular students academic year 2010 to 2012. The results of the research obtained : 1) activities have a positive and significant impact on studentâs independence. 2) Interest have a positive effect but not significant on studentâs independence and 3) Opinion have a positive effect but not significant on studentâs independency. Keywords: studentâs independence, Activities, Interest , Opinion and lifestyle